Immunization as an entry point for primary health care and beyond healthcare interventions—process and insights from an integrated approach in Lebanon - Kapuria, Bhrigu; Hamadeh, Randa S.; Mazloum, Farah; Chaalan, Kassem; Aung, Kyaw; Higgins, Ettie; Kanaan, Wafaa; Tohme, Tatiana; Kamal, Doaa; Khoury, Christina E.; Syed, Sabin (Frontiers in Health Services, 2023)
Integrated healthcare systems are continually pitched as the major contributor towards better distribution of health outcomes and enhanced well-being. In emergency conditions integrated health care services can guarantee better access to the target population. In recent years the multitude of crisis i.e., economic collapse, fuel crisis, Beirut blast, large refugee population and COVID-19 pandemic in Lebanon has led to a major shift in health seeking behavior of the communities, with preventive services being put into last priority despite being available, and curative healthcare services also being seek at as late as possible. Extensive drop in immunization coverages and overstretched public health system presents the risk of Vaccine Preventable Disease outbreak and needed urgent intervention to bridge the immunity gap. Ministry of Public Health, Lebanon and UNICEF Lebanon successfully demonstrated the use of immunization platform as an entry point to reach communities for service delivery, identification and referral, screening, awareness generation and a host of other services that can be liked for other programs including but not limited to Maternal and Child health, nutrition, early childhood development, COVID-19, children with disabilities, social protection, education, health emergencies like cholera etc. and can provide bi-directional support to each other. UNICEF along with MoPH (Ministry of Public Health) has been working towards reaching the most vulnerable population with a bouquet of services through existing immunization touch points, for favorable healthcare outcomes.